Szarvas Pál kémia professzor élete és munkássága - Brücher, Ernő (Gerundium, 2018)
The Life and Work of Pál Szarvas, Professor of Chemistry. At the University of Debrecen, the Faculty of Science was founded in 1949. The management boards of the new Faculty and of the University spared no effort to bring prominent scientists as leading members of the newly organized science departments. In this manner, Pál Szarvas was also invited in 1951 to come to Debrecen to be the Head of the Department of Inorganic and Analytical Chemistry. His first task here was to organize the furnishing and equipment of the student and research laboratories, to initiate classroom teaching and research work despite the rather unfavourable financial conditions. From 1952 on the number of staff members began to increase and from the mid-1960s the level of the laboratory equipment was also improving. Research work was launched in the field of analytical chemistry, where various methods were developed for the determination of some rare metals in the presence of larger amounts of other elements. From the end of the 1960s the main research field of the Department was solution chemistry, the equilibrium and kinetic studies on the formation of complexes of transition metals and lanthanides with organic ligands. Another developing field was the synthesis and study of new boron-organic compounds. The focus of research in analytical chemistry shifted to the use of emission spectrography and atomic absorption spectrophotometry. Professor Szarvas was also involved in the leadership of the Faculty and of the University. He was Dean of the Faculty (1954–58) and the Rector of the University (1963–66). His activity was highly important in the preparation of the construction of the chemistry building. Professor Szarvas, who retired in 1975, played a significant role in the organization of the teaching and research work of the Department of Inorganic and Analytical Chemistry, which has exerted an important impact on the current existence and successes of the Department.